2013
DOI: 10.1103/physrevb.88.235313
|View full text |Cite
|
Sign up to set email alerts
|

High-Qresonant modes in a photonic crystal heterostructure nanocavity and applicability to a Raman silicon laser

Abstract: When a heterostructure is created at the center of a photonic crystal line-defect cavity to form a nanocavity, the photonic band gap contains several high-quality (Q) factor resonant modes. We have studied the optical properties of these modes to examine their applicability to Raman silicon lasers, which require two high-Q resonant modes with a frequency spacing of 15.6 THz. Our experimental and numerical analyses reveal four types of resonant modes. We demonstrate that pairing the resonant mode originating fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Since Raman Si lasers enable continuous-wave (cw) operation at room temperature in the telecommunication wavelength regime [13][14][15], they are attractive for information technologies. We have developed a Raman Si laser based on a highquality-(high-Q)-factor photonic-crystal (PC) nanocavity with a resonator size of 10 µm that enables an ultralow threshold of approximately 1 µW [16,17]. Such a small, low-threshold device is suited for dense integration on Si photonic circuits, which can be employed for applications such as cw laser sources and all-optical switching devices.…”
Section: Introductionmentioning
confidence: 99%
“…Since Raman Si lasers enable continuous-wave (cw) operation at room temperature in the telecommunication wavelength regime [13][14][15], they are attractive for information technologies. We have developed a Raman Si laser based on a highquality-(high-Q)-factor photonic-crystal (PC) nanocavity with a resonator size of 10 µm that enables an ultralow threshold of approximately 1 µW [16,17]. Such a small, low-threshold device is suited for dense integration on Si photonic circuits, which can be employed for applications such as cw laser sources and all-optical switching devices.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocavities consist of a line defect of 27 missing air holes. They are fabricated along the [100] direction of the (100) SOI substrate in order to enhance the Raman gain . By comparing the present SEM images with those from the high‐ Q cavities in the previous Section 4.1, it can be confirmed that the different direction of the nanocavity used in the Raman laser does not influence the fabrication accuracy.…”
Section: Resultsmentioning
confidence: 58%
“…The increase of a leads to a decrease in the band frequencies of the two propagation modes for the line defect as shown in Figure b. As a result of mode gap confinement, two nanocavity modes are formed . The low‐ and high‐frequency modes are referred to as the 1st and 2nd nanocavity mode, respectively.…”
Section: Nanocavity Structurementioning
confidence: 98%
See 1 more Smart Citation
“…One-dimensional photonic crystal (1DPC) is a well-known concept with broad fields of application since their discovery in 1987 [1,2]. Their initial development was motivated to improve laser and optical fiber technologies [3][4][5], but today they have been extended to other commercial devices, like optical filters [6,7], high Q-photonic cavities [8,9], photocatalysis [10,11], high-temperature sensitive sensors [12], magnetoplasmonics [13], metamaterials [14], light tailoring [15], or even energy functionalization. [16].…”
Section: Introductionmentioning
confidence: 99%